PENGARUH LATIHAN RENTANG GERAK TERSTRUKTUR DENGAN KEMAMPUAN FUNGSIONAL PADA PASIEN YANG MENGALAMI GANGGUAN MOBILITAS - Noventa Siskarya Ginting; Wasisto " Utomo; Herlina " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractStroke is a clinical syndrome that characterized by the sudden development of persistent focal neurological deficit secondary to vascular events.The aim of this study was to determine the effect of structured range of motion exercises to functional ability in stroke patients with mobility. Research method was using a quasi-experimental design with Non Eqiuvalent Control Group Design. This study was conducted in outpatient of Neural Polyclinic in Arifin Achmad Pekanbaru Hospital 30 respondents.15 respondents experimental group and 15 respondents to the control group that taken by inclusion and exclusion criteria by using consecutive sampling techniques. Measuring instruments were using Barthel index questionnaires and standardized observation sheet. The analysis is used univariate analysis to determine the frequency distribution and bivariate test using t dependent and independent. The results of this study showes a significant increase in the average functional capabilities of pre and post intervention in the experimental group (p value = 0.000). It can be concluded that there is effect of structured range of motion in patients with stroke that has impairing mobilization. The result of this study is expected to be material information and it provides nurse to apply structured range of motion to improve functional ability in stroke patients.Keywords                 : Barthel index, exercises structured, stroke, functional ability